Greenhouse Gas Emissions in Bangladeshi Rice Cultivation: Impact of Water Management Practices - Habib, Muhammad Ashraful; Islam, S.M. Mofijul; Nayak, Swati; Chandel, Amaresh; Bhosale, Sankalp; Salvo, Stella; Singh, Vikas Kumar (International Rice Research Institute, 2025)
Direct-seeded rice (DSR) is a promising method for reducing water use, labor, and greenhouse gas (GHG) emissions compared to transplanted rice. However, its impacts on rice yield and GHG emissions in Bangladesh are not well documented. This study conducted multi-location field experiments in Rajshahi and Rangpur during the late Boro and Aus seasons of 2023-2024. The experiments compared dry DSR, transplanted rice with flooded irrigation (TFR), and transplanted rice with alternate wetting and drying irrigation (TAD) on rice yield and GHG emissions. Methane (CH4) emissions were measured using a closed gas chamber technique and analysed with a gas chromatograph. Results showed that DSR significantly reduced CH4 emissions by 11-21% in Rajshahi and 23-40% in Rangpur compared to TAD and TFR. Higher emission factors, yield-scaled emissions, and global warming potential (GWP) were found in TFR compared to DSR and TAD. Total CH4 emissions and GWP varied significantly between Rajshahi and Rangpur. However, DSR reduced grain yield by 21-28% in Rangpur, while yields were comparable among treatments in Rajshahi. The Rajshahi site had significantly higher yields than Rangpur. This study highlights the trade-offs between environmental benefits and crop productivity in different regional contexts.